Legal Analysis Of Legal Protection For Victims Of Violence In Marriage - Nur Balqis; Rahul Ardian Fikri; Fitria Ramadhani (International Journal of Sociology and Law, 2024)
In Constitution Number 23 Year 2004 about Deletion Violence In House ladder in explain that violence in House ladder is every action to somebody especially Woman , Which result the emergence misery or suffering in a way physique , sexual , psychological , and/ or neglect House ladder including threat For do act , coercion , or robbery independence in a way oppose law in scope House stairs . This study aiming For do analysis law to protection law towards victims of crime violence in House ladder . This study focus on the framework law related victim protection in context marriage . The research method used is method normative law meaning study This use approach legal that is a the attempted approach with observe and pay attention existence applicable law and analysis​ various regulation legislation and decisions relevant courts​ with him . The results of the study show that although Already There is regulation For protecting victims of violence in House stairs , its application Still face Lots constraint . A number of aspect important from analysis This concerning effectiveness laws that protect women and children , as well as role enforcement law in handle case violence in House stairs . With background behind said , research This emphasizes expansion and refinement​ regulations , improvements awareness community , and participation active apparatus enforcer law For ensure greater victim protection effective . In short , protection law against victims of violence in House ladder need effort together between government , law enforcement law and society For create a safe and supportive environment for all victims of crime violence in House ladder .